China's golden shield corporations and the development of surveillance technology in The People's Republic of China - Walton, G (International Centre for Human Rights and Democratic Development, 2001)
Information and communication technology is often described as the driving force behind globalization. It is also promoted as a tool for democratization with connectivity heralded as the end of the digital divide. In truth, there is no doubt that electronic communication has facilitated the flow of information around the globe and that it has increased opportunities for human rights and democracy activists to build international support for their struggles. Unfortunately, the advent of modern communication technology has also brought new challenges for human rights advocates, particularly those living under repressive regimes. In a world where the rules of international trade are unconnected to international human rights law, technology’s promise of democratization is threatened by economic priorities. In the People’s Republic of China, where there is no democratic accountability or legislative protection of human rights, technology can be and has been used as an instrument of repression. At stake is the right of all people to an international order within which the promise of the Universal Declaration of Human Rights (UDHR) can be fulfilled. The UDHR and its accompanying covenant on civil and political rights protect fundamental human rights including the individual’s right to privacy. The protection of human rights is the obligation of governments and must be reflected in all activities implemented under governmental authority whether they are trade promotion activities, the negotiation of bilateral and international trade agreements, export financing or development assistance. This report reveals how sophisticated technology, developed in Canada and promoted through a series of national and international processes, could undermine the principles enshrined in human rights agreements. China’s Golden Shield project threatens the protection of human rights, in particular the right to privacy – a right that underpins other essential elements of democracy activism such as freedom of association and freedom of expression. It positions the alliance of government and business in opposition to those standing on the cyber-frontline of the human rights movement in China today. It is my hope that this paper will provide a glimpse into the world of high-tech, big business and the struggle for human rights and democracy in China. On behalf of Rights & Democracy, I offer it in the spirit of solidarity with the people of China who may find its content of some use as they develop and consolidate social movements for change. I offer it also to my fellow Canadians who, following recent reports on police surveillance of dissent in Canada, may discover how intimately the rights of citizens in China are linked to our own.